وظيفة ودلالات حروف الجر في التراكيب اللغوية - الحاج الزاكي, آدم محمد أحمد; إسماعيل موسى, عباس محمد; عوض الكريم, إجلال محمد (Gezira Journal of Educational Sciences and Humanities; مجلد 21 عدد 2 (2024), 2026)
هدف البحث إلى إبراز مكانة حروف الجر في البناء اللٌّغوي ودورها في التراكيب اللُّغوية المختلفة للحاجة إليها في التعبير عن العلاقات اللُّغوية المختلفة، نحو دلالتها على الزمان أو المكان، أو علاقة الفاعلية أو المفعولية وربط الأسماء بالأسماء، والأسماء بالأفعال، وبيان ما تقوم بها من وظائف نحوية ودلالات لغوية، مثل الربط بين المضاف والمضاف إليه، والاختصار في الكلام، إضافة إلى الوظيفة البنائية، والوقوف على الخلاف النحوي واللغوي في إنابة حروف الجر بعضها عن بعض في الدلالة، و التعرف على ما استند عليه كل فريق من الحجج لإثبات رأيه والمترادفات التي استعملت للدلالة على الإنابة، مثل التوسع والتضمين والتناوب، والتعرف على مواطن زيادة حروف الجر ودورها في انسجام العبارات وتركيبها وتتبع الاستعمالات المعاصرة للحروف وإظهار الحالات التي تخالف فيها الاستخدام السليم. اتبع الباحث  المنهج الوصفي الاستقرائي التحليلي. وتوصل إلى النتائج الآتية: إن حروف الجر أنشط الحروف العاملة وأكثرها حيوية لصلتها بالأسماء واختصاصها بها، كثير من العلاقات التركيبية في البناء اللُّغوي والنحوي لا تتم إلا بوجود حروف الجر، مثل علاقة الفاعلية والمفعولية، والعلاقة المكانية والزمانية، لحروف الجر وظائف أخرى تقوم بها، منها الاختصار في الكلام، النحاة على امتداد تاريخ النحو مختلفون في دلالات حروف الجر مما انعكس على تفسير القرآن الكريم،  لا يفهم من زيادة بعض حروف الجر في البناء اللُّغوي أنه لا عمل لها، بل هناك زيادة في المعنى لا يتحقق من دونها. توصي الدراسة بإخضاع حروف الجر إلى مزيد من الدراسات التطبيقية في القرآن الكريم، والنصوص الأدبية، البحث عن أسباب الخلاف بين النحاة حول دلالات حروف الجر، حصر الأخطاء الشائعة في استخدامات حروف الجر. The aim of the research is to highlight the status of the letters in syntax and its role in the different linguistic structures of the need to express different linguistic relations, such as the indication of time and place, the relationship of effectiveness or effectiveness, and the connection of names by names and names by deeds, , As well as the link between the additive and the addition, and the shortness of speech, in addition to the structural function, and to find the dispute about the assignment of the letters of the drafts of each other in significance, and the basis of each team to establish his views and synonyms used to indicate the assignment, Such as expansion, inclusion and rotation, identification of the characters of the increase in the letters and their role in the harmony of the phrases and their composition, tracking the contemporary uses of the letters and showing cases where the proper use is violated. The study followed the analytical descriptive method. And found the following results: that the letters of the most active letters and most vital to their relationship to the names and competence of them, that many of the structural relationships in the construction of language is done only with the presence of prepositions, such as the relationship of effectiveness and effectiveness, and the spatial relationship and temporal, Including the shortening of speech, the grammarians along the history of the grammar are different about the meanings of the letters of imprint, which reflected the interpretation of the Koran. Does not understand the increase of some of the letters in syntax that it does not work for them, but that there is an increase in meaning cannot be achieved without it. The study recommends the following: To subject the prepositions to more applied studies in the Holy Quran and literary texts, to search for the causes of disagreement between the grammarians on the meanings of the letters of the alphabet, to identify the common mistakes in the use of the letters of the alphabet.